Exploring Motivation of English Students to Choose a Non-teaching Career: A Case Study of 2021 Undergraduate Students at English Education, FKIP UNRAM - Rahmadi, Andrian; Waluyo, Untung; Susanti, Ni Wayan Mira (LITPAM, 2026)
The Faculty of Teacher Training and Education (FKIP) is established to prepare professional teachers and trainers who meet national education standards. At University of Mataram, the English Education program under FKIP offers several research interests as part of their academic development. These research interests are introduced when students reach the fifth semester. At this stage, students are expected to think carefully about their future careers. There are five research interests available in total. These interests are grouped into two main categories, namely teaching and non-teaching concentration. The teaching concentration includes teacher candidates and course instructors. This track is mainly designed for students who want to become English teachers. Meanwhile, the non-teaching concentration includes tourism, translation and interpretation, and research. These options allow students to apply English skills outside formal education. This study examines the intrinsic and extrinsic motivation that influence students to choose non-teaching concentrations despite being enrolled in a teacher training faculty. Guided by Self Determination Theory (SDT), this study employed a qualitative case study design. Data were collected through open-ended questionnaire and semi structured interview at FKIP UNRAM, targeting undergraduate students of the year 2021. A total of 86 responses were collected, representing 55,4% of the total amount of population (155 students). Thematic analysis by Braun & Clarke was used to analyze 86 responses. The findings show that 26 (16,77%) students were primarily intrinsically motivated, 43 (27,74%) students were extrinsically motivated, and 17 (10,96%) students were influenced by both. These findings highlight a range of motivational influences and suggest that many students prefer non-teaching concentration due to various intrinsic and extrinsic factors, even within a teacher-focused academic environment.